PENGARUH PERMAINAN CUP STACKING TERHADAP KETANGKASAN TANGAN (MOTORIK HALUS) SHAREFIT SURABAYA - Sahara, Aldella Minja; Rusdiawan, Afif; Pudjijuniarto; Panji Bana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The purpose of this research was to analyze the influence of cup stacking games on participants’ fine motor skills, specifically to (1) measure changes in hand speed and hand–eye coordination, (2) evaluate the effectiveness of cup stacking as a fine motor stimulator, and (3) provide practical recommendations for implementing this activity in educational or recreational fitness settings. The study employed an experimental design using a pretest–posttest control group method. A total of 20 participants aged 6–10 years were purposively selected and equally divided into control and experimental groups. Both groups completed a standardized fine motor test before and after the intervention. The experimental group received cup stacking training for three weeks (three sessions per week, 40 minutes each), consisting of progressive coordination and reflex exercises. Data were analyzed using parametric statistical tests after normality and homogeneity assumptions were confirmed. The Paired Samples t-Test showed a significant difference between pretest and posttest scores (t = −5.891, p < 0.001), indicating that cup stacking effectively improved participants’ fine motor abilities. However, the Independent Samples t-Test revealed no significant difference between the control and experimental groups (p = 0.137), suggesting that both groups improved, but not to a statistically distinct degree. These findings confirm that cup stacking has a positive and measurable influence on fine motor enhancement through repeated, coordinated, and visually guided hand movements. The activity stimulates motor learning processes, supports neuromuscular adaptation, and can be implemented as a low-cost and engaging training method in educational or recreational environments. In conclusion, cup stacking represents an innovative and enjoyable approach for fine motor development, encouraging further research with larger samples, longer interventions, and advanced assessments such as biomechanical or neurophysiological analyses to explore its broader impact on motor performance.